Poeira X Unicon: confrontos e contrapontos entre expropriados e Itaipu - Mascarenhas, Milena Costa (2011)
This research worked with the theme of Itaipu hydroelectric plant construction, in western Parana, built during the period of military dictatorship between 1975 and 1984. The research aimed to analyze the public speech through information Unicon, the first newspaper in Itaipu created in 1978 and confront it with the newsletter Poeira, created in the same year, produced by the Pastoral Land Commission. We attempted to identify the projects delivered by these two devices: the Unicon as official spokesman that Itaipu used to build a hegemonic consensus through a speech that propagated the image of Brazil as a strong country, a country of the future, rich in natural resources and urged Brazilians to contribute to its growth, justifying the sacrifices that featured work; and newsletter Poeira with a counter-hegemonic discourse that contested and denounced Itaipu's actions, becaming the main instrument the expropriated had to share their experiences, develop views, denounce the pressures faced by Itaipu and from those proposed action project for the movement of those affected